Baronesa de Três Serros: parte da história da cidade de Pelotas - Wazenkeski, Verlaine Fátima (2017)
This research work, developed within the scope of the UFSM Cultural Heritage Masters, was carried out with the objective of analyzing the life of Amélia Fortunata Hartley de Brito, Baroness of the Three Hills, from 1864, the year of her arrival in the city of Pelotas in Rio Grande do Sul, from the far-away city of Rio de Janeiro, where she lived with her parents and grandparents. Considered a lady from Pelotas society, today she has a museum dedicated to her memory, the Museum of the Baroness; she was very present like a dedicated social woman in the period between 1864 and the end of the first decade of XX century, in the city of Pelotas / RS.The aim was to identify the references and possible contributions of the Baroness in the cultural heritage of Pelotas, analyzing her social and political importance. From this analysis, a glossary of period terms was created to contribute to the formal and non-formal educational practices of the said museum in order to value not only the historicity, but also the corresponding social memories contained in this period.